West Asian communities in the Philippines an exploratory study of migrant Iranians, Jews, Arabs, and Turkish. - Sevilla, Henelito A. Jr. (2015)
Although citizens of West Asian countries have lived and integrated into Philippine society since the latter part of the nineteenth century, only a handful of Filipino or foreign scholars have touched on the phenomenon. There has been much previous academic research on the study of Islam in the Philippines, but less on the migratory movements of West
Asian peoples and their struggles to successfully integrate into Philippine society. To help address this gap, this paper attempts to profile the West Asian communities, most particularly of Iranians, Arabs, Jews, and Turkish, in Metro Manila and nearby areas. It seeks to chart the stages of migrations; identify successful personalities from West Asian communities; elucidate the motivations for settlement; discuss migrants’ links to their countries of origin; and bring to light the challenges they face while living in the Philippines.
Keywords: Migrations; Migrations, Jewish